Transmembrane Protein TMEM230, a Target of Glioblastoma Therapy - Cocola, Cinzia; Magnaghi, Valerio; Abeni, Edoardo; Pelucchi, Paride; Martino, Valentina; Vilardo, Laura; Piscitelli, Eleonora; Consiglio, Arianna; Grillo, Giorgio; Mosca, Ettore; Gualtierotti, Roberta; Mazzaccaro, Daniela; et al. (Frontiers in Cellular Neuroscience, 2021)
Glioblastomas (GBM) are the most aggressive tumors originating in the brain. Histopathologic features include circuitous, disorganized and highly permeable blood vessels with intermittent blood flow. Permeable blood vessels may contribute to the inability to direct therapeutic agents to tumor cells. Current known targets for anti-angiogenic therapies provide limited effect in improvement in overall survival of 12 to 15 months following diagnosis. Identification of novel targets for anti-angiogenic therapy remains an important goal. We previously demonstrated in an animal model that a balanced level of expression of the transmembrane protein TMEM230/C20ORF30 was required for normal blood vessel structural integrity and proper network formation. To investigate whether TMEM230 may be involved in the pathogenesis of GBM, we analyzed its prognostic value in patient tumor gene expression datasets and performed functional analysis. TMEM230 was found to be necessary for growth of U87 cells, a model of human GBM. Down regulation resulted in loss of U87 migration and 2D and 3D substratum adhesion capacity and inability to sustain re-passaging of U87 cells. Conditioned media of U87 expressing TMEM230 induced sprouting and tubule-like structure formation of HUVECs. Moreover, TMEM230 promoted vascular mimicry like behavior of U87 cells in vitro. Gene expression analysis of 702 patients with gliomas identified that TMEM230 expression levels distinguished high grade from low grade tumor entities. Patient bioinformatic analysis revealed molecular pathways consistent with the properties observed in in vitro U87 cell assays. Within low grade gliomas, elevated TMEM230 levels correlated with reduced overall survival independent of the tumor subtype. Analysis of TMEM230 expression also indicated that the highest level of TMEM230 expression was correlated in glioblastoma with genes associated with ATP dependent microtubule kinesin motor activity, providing directions for future functional analyses. Our studies support that TMEM230 has both tumor intracellular and extracellular functions, and that elevated levels of expression of TMEM230 promotes tumor cell migration and hypervascularization of tumor tissue with aberrant blood vessel formation and structure. Down regulation of TMEM230 expression inhibits both low grade glioma and glioblastoma tumor progression. TMEM230 therefore is promising anticancer therapeutic target for inhibiting both GBM tumor cells and tumor driven angiogenesis.